Future Time Orientation and Learning Engagement Through the Lens of Self-Determination Theory for Freshman: Evidence From Cross-Lagged Analysis - Peng, Michael Yao-Ping; Zhang, Zizai (Frontiers in Psychology, 2022)
View of future time orientation is a cognitive construct about future time. This view has its unique work of motivation, and effect of academic performance. Previous studies have only explored the influence that future time orientation brings to the learning process at a single time, and most of them focus on cross-sectional studies. To further explore the cross-lagged relationship for freshmen between future time orientation and learning engagement during different periods, AMOS 23.0 was performed for cross-lagged analysis in this study to explore the influence and effect among variables of different periods. This research is based on the theory of self-determination to discover the relationship between future time and learning involvement for freshmen in enrollment and the first summer vacation. In this research, there are 1000 valid samples in the first stage and 840 valid samples in the second stage for the conduction of descriptive statistics, pair t-Test, and cross-lagged analysis. The results show that: (1) For learning engagement, freshmen at the end of first year have higher average score than the beginning of first year. (2) Students' view of future time orientation can affect their learning engagement of future through students' self-determination. At last, we provide some suggestions as reference for institutional research and future research.